2017
DOI: 10.3389/fpsyg.2017.01368
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Potential Flexibility and Practical Flexibility in Equation Solving

Abstract: Researchers interested in mathematical proficiency have recently begun to explore the development of strategic flexibility, where flexibility is defined as knowledge of multiple strategies for solving a problem and the ability to implement an innovative strategy for a given problem solving circumstance. However, anecdotal findings from this literature indicate that students do not consistently use an innovative strategy for solving a given problem, even when these same students demonstrate knowledge of innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 41 publications
3
51
1
1
Order By: Relevance
“…Similarly, previous studies have shown that what students do on a standard task (their strategic behavior) does not fully reflect what they know (their strategic knowledge) (e.g., Blöte et al 2001). Xu et al (2017) recently found this so-called potential flexibility (what students know) and practical flexibility (what students do) in the domain of equation solving to be distinct but related. The current study only measured practical flexibility, ignoring potential flexibility.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, previous studies have shown that what students do on a standard task (their strategic behavior) does not fully reflect what they know (their strategic knowledge) (e.g., Blöte et al 2001). Xu et al (2017) recently found this so-called potential flexibility (what students know) and practical flexibility (what students do) in the domain of equation solving to be distinct but related. The current study only measured practical flexibility, ignoring potential flexibility.…”
Section: Discussionmentioning
confidence: 80%
“…Strategic flexibility and adaptivity are considered important components of mathematical proficiency (e.g., Baroody 2003;Xu et al 2017). Although many different definitions and operationalizations exist in the literature, they converge on two central themes: the knowledge of different solution strategies and the ability to adapt them appropriately when solving a problem (Rathgeb-Schnierer and Green 2017).…”
Section: Adaptivity Flexibility and Shortcut Strategiesmentioning
confidence: 99%
“…The mathematical flexibility assessment ( Xu et al, 2017 ) consisted of 12 linear equations (see Table 1 ). Drawing on prior research on flexibility in linear equation solving (e.g., Star and Seifert, 2006 ; Rittle-Johnson and Star, 2007 ), the assessment included four types of equations, each of which can be solved using both a standard algorithm and a more innovative approach that takes advantage of specific numerical or structural features of the problem to arrive at a solution more efficiently.…”
Section: Methodsmentioning
confidence: 99%
“…Solving problems flexibly and adaptivelywhich requires students to know multiple strategies and to shift between strategies based on the problem context so that the problem can be solved in the most efficient wayhas been recognized as an important goal in mathematics learning and thinking (Heinze, Star, & Verschaffel, 2009;Heirdsfield & Cooper, 2002;National Research Council & Mathematics Learning Study Committee, 2001;Star & Rittle-Johnson, 2008;Star & Seifert, 2006;Verschaffel, Luwel, Torbeyns, & Van Dooren, 2009;Xu et al, 2017). Students who develop mathematical flexibility are more capable of utilizing their procedural knowledge to solve novel problems, and they also show a greater understanding of mathematics concepts (Bl€ ote, Van der Burg, & Klein, 2001; Rittle-Johnson, Star, & Durkin, 2012).…”
mentioning
confidence: 99%
“…Moreover, flexibility is a key character of the development of mathematics expertise (Baroody, 2003;Star & Newton, 2009). However, studies have found that too many students persevere in using a single, sometimes nonoptimal, strategy to solve many similar problems, perhaps only switching strategies to a more efficient one when explicitly prompted to do so (Hickendorff, 2018;Newton, Lange, & Booth, 2019;Star & Rittle-Johnson, 2008;Star & Seifert, 2006;Xu et al, 2017).…”
mentioning
confidence: 99%